Louise Petrén – A Mathematician Whose Work Waited for a Century to Be Appreciated - Emelyanova, Inna S. (Journal of Vibration Testing and System Dynamics, 2026)
Louise Petrén (Hedvig Louise Beata Petrén-Overton, 1880-1977) was the first Swedish woman to defend her doctoral thesis in mathematics in 1911. It took nearly a hundred years for her thesis to be duly appreciated.